A new promising phylogenetic marker to study the diversity of fungal communities: The Glycoside Hydrolase 63 gene. (12th May 2017) - Pérez‐Izquierdo, L.; Morin, E.; Maurice, J. P.; Martin, F.; Rincón, A.; Buée, M.
Abstract: In molecular ecology, the development of efficient molecular markers for fungi remains an important research domain. Nuclear ribosomal internal transcribed spacer (ITS) region was proposed as universal DNA barcode marker for fungi, but this marker was criticized for Indel‐induced alignment problems and its potential lack of phylogenetic resolution. Our main aim was to develop a new phylogenetic gene and a putative functional marker, from single‐copy gene, to describe fungal diversity. Thus, we developed a series of primers to amplify a polymorphic region of the Glycoside Hydrolase GH63 gene, encoding exo‐acting α‐glucosidases, in basidiomycetes. These primers were validated on 125 different fungal genomic DNAs, and GH63 amplification yield was compared with that of already published functional markers targeting genes coding for laccases, N ‐acetylhexosaminidases, cellobiohydrolases and class II peroxidases. Specific amplicons were recovered for 95% of the fungal species tested, and GH63 amplification success was strikingly higher than rates obtained with other functional genes. We downloaded the GH63 sequences from 483 fungal genomes publicly available at the JGImycocosm database. GH63 was present in 461 fungal genomes belonging to all phyla, except Microsporidia and Neocallimastigomycota divisions. Moreover, the phylogenetic trees built with both GH63 and Rpb1 protein sequences revealed that GH63 is also a promising phylogenetic marker. Finally, a very high proportion of GH63 proteins was predicted to be secreted. This molecular tool could be a new phylogenetic marker of fungal species as well as potential indicator of functional diversity of basidiomycetes fungal communities in term of secretory capacities.